TATBIQU TADRISI KITABI (TAKALUM AL-ARABIYATI) ‘ALAA AT-TULAABI AL-MUBTADIIYN AL-'AAJAM: تطبيق تدريس كتاب (تكلم العربية) على الطلاب المبتدئين الأعاجم - Shady Elsayed; Asep Sopian; M Syarifuddin (Cordova Journal, 2024)
This research deals with the application of teaching the Arabic language to non-Arab beginners using the new book (Takalam Al Arabiyah), which was written by the researcher himself. This research aims to introduce the book and explain its contents, clarify the advantages of the book over other books, and explain the students’ response to teaching with the book. The researcher will rely on the descriptive approach in this research to know the students’ response to teaching with the book through the questionnaire tool. At the end of it, the researcher concluded that the book (Takalam Al Arabiyah) is suitable for non-Arabic beginners in terms of its content, design, presentation method and objectives. Thus, this book can be an educational material for beginning students and a reference for teachers who want a new teaching book as well.